If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 5(3x + -4) = 7(x + -12) Reorder the terms: 8 + 5(-4 + 3x) = 7(x + -12) 8 + (-4 * 5 + 3x * 5) = 7(x + -12) 8 + (-20 + 15x) = 7(x + -12) Combine like terms: 8 + -20 = -12 -12 + 15x = 7(x + -12) Reorder the terms: -12 + 15x = 7(-12 + x) -12 + 15x = (-12 * 7 + x * 7) -12 + 15x = (-84 + 7x) Solving -12 + 15x = -84 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -12 + 15x + -7x = -84 + 7x + -7x Combine like terms: 15x + -7x = 8x -12 + 8x = -84 + 7x + -7x Combine like terms: 7x + -7x = 0 -12 + 8x = -84 + 0 -12 + 8x = -84 Add '12' to each side of the equation. -12 + 12 + 8x = -84 + 12 Combine like terms: -12 + 12 = 0 0 + 8x = -84 + 12 8x = -84 + 12 Combine like terms: -84 + 12 = -72 8x = -72 Divide each side by '8'. x = -9 Simplifying x = -9
| -8(2n-4)+5= | | -7n+4(-6+3n)= | | 10d+5d=2 | | 4x^2-40x+103=0 | | -3-8(-5a-1)= | | 2x-5(x+2)=-8-2x | | .50t+.33t=10 | | -3-8(-5-1)= | | 2-c=-6c+-3 | | 9a-4(2a+5)= | | -(x+1)=2(5-x) | | -12=2+7v | | 49.8-6-18.8= | | 2*cos(4x)=0 | | x^2-2x-15624=0 | | 9a-4(-5a-1)= | | 0.3y^2+0.7y^2-0.2y^2= | | 72=90-x | | 8-3(6-6x)= | | .4x-.9y=.7 | | 9=2(4-x)+7 | | 3x(4x+3)= | | 13x-7=42+6x | | 12r+36=2r+10-3r | | (x-9)(x-9)=0 | | (8a+6)2=34 | | 13-8y=5y+2 | | 2c+3=4c-4 | | 150=4.5t | | (18-7)+1=-9 | | 20+2n=52 | | 81-18s+s^2=0 |